Tree water uptake on suction distribution in unsaturated tropical residual soil slope - Mohd Fakhrurrazi, Ishak (2014)
This study provides an investigation of active root tree zone located at the toe of a slope. This section and its vicinity generated matric suction due to tree water uptake on tropical residual soil slope. The research employed several approaches i.e field monitoring, laboratory experimental and numerical modelling. A field monitoring was carried out to collect matric suction data at the slope with two conditions; in absence of a tree and with a tree located at the toe of a slope. The unsaturated shear strength behaviour of soil under different stress level is investigated, using uncomplicated testing procedure subject to actual matric suction encountered during field monitoring. The numerical simulation modelling was applied based on the laboratory results to obtain the most appropriate condition to replicate the tree water uptake within the soil slope. A decrease in matric suction occured after a long duration of intense rainfall. This condition was function as an initial condition before the water uptake driven by active root tree generated to the maximum matric suction (low moisture content). The pattern of matric suction profiles revealed that majority of matric suction changes was greater at the proximity of tree trunk below 4 in and at a shallow depth of 0.5 m. Transpiration on single mature tree has significantly altered the matric suction or moisture variation distribution on an unsaturated soil slope. This study also illustrated the nonlinear relationship between the apparent shear strength and suction influencing the stability of the slope. The assessment of slope stability due to the influence of a tree induced suction was provided in this research. The factor of safety against slope failure has improved up to 63 % on slope with tree at toe compared to a slope without tree. Lastly, the numerical simulation modelling of matric suction induced by a tree has been verified through comparison to actual field monitoring results recorded during the dry period. Generally, an acceptable aggrement between simulation and field monitoring results has been achieved. This research delivers a strong belief that a preserved mature tree can improve soil properties in slopes designs.